An experimental study on fire characteristics of urban complex underground space based on BIM - Jinrong Cui; Hao Mei; Haosen Sun; Ye Jingqi; Wei Hu; Yong Xu (CAAI Transactions on Intelligence Technology, 2023)
Abstract Compared with the space on the ground, if there is a fire in the urban complex underground space, the loss will be greatly harmful. In addition, the complex underground space is usually connected with other large space areas and densely populated. Once a fire occurs in the complex underground space, it will cause huge property losses and casualties. In order to reduce the risk of fire, it is necessary to deeply understand the development rules and characteristics of fire in the complex underground space of the city. This article has mainly carried on the following work: (I) A particularly complex model of the multi‐storey subway station was built. On this basis, three groups of comparative experiments were conducted to study the effects of fire power, fire location and smoke control system on fire development, and the conclusion that fire location is the most important factor for fire development was obtained; (II) In order to explore the entire space fire and the local space fire, CFD (Computational Fluid Dynamics) is used to build a large‐size fire model and a small‐size fire model respectively; (III) Multiple detector data as temperature slices were built, and it is expected to make full use of the simulation data to deduce the important index of fire location in the early stage of fire. All of the works in this paper will provide reference experimental data for the prevention and firefighting of a sudden fire in the complex underground space.